Anemia Increases Oxygen Extraction Fraction in Deep Brain Structures but Not in the Cerebral Cortex - Shen, Jian; Miao, Xin; Vu, Chau; Xu, Botian; González-Zacarías, Clio; Nederveen, Aart J.; Wood, John C. (Frontiers in Physiology, 2022)
Sickle cell disease (SCD) is caused by a single amino acid mutation in hemoglobin, causing chronic anemia and neurovascular complications. However, the effects of chronic anemia on oxygen extraction fraction (OEF), especially in deep brain structures, are less well understood. Conflicting OEF values have been reported in SCD patients, but have largely attributed to different measurement techniques, faulty calibration, and different locations of measurement. Thus, in this study, we investigated the reliability and agreement of two susceptibility-based methods, quantitative susceptibility map (QSM) and complex image summation around a spherical or a cylindrical object (CISSCO), for OEF measurements in internal cerebral vein (ICV), reflecting oxygen saturation in deep brain structures. Both methods revealed that SCD patients and non-sickle anemia patients (ACTL) have increased OEF in ICV (42.6%±5.6% and 30.5%±3.6% in SCD by CISSCO and QSM respectively, 37.0%±4.1% and 28.5%±2.3% in ACTL) compared with controls (33.0%±2.3% and 26.8%±1.8%). OEF in ICV varied reciprocally with hematocrit (r2 = 0.92, 0.53) and oxygen content (r2 = 0.86, 0.53) respectively. However, an opposite relationship was observed for OEF measurements in sagittal sinus (SS) with the widely used T2-based oximetry, T2-Relaxation-Under-Spin-Tagging (TRUST), in the same cohorts (31.2%±6.6% in SCD, 33.3%±5.9% in ACTL and 36.8%±5.6% in CTL). Importantly, we demonstrated that hemoglobin F and other fast moving hemoglobins decreased OEF by TRUST and explained group differences in sagittal sinus OEF between anemic and control subjects. These data demonstrate that anemia causes deep brain hypoxia in anemia subjects with concomitant preservation of cortical oxygenation, as well as the key interaction of the hemoglobin dissociation curve and cortical oxygen extraction.